2021
DOI: 10.24018/ejedu.2021.2.1.21
|View full text |Cite
|
Sign up to set email alerts
|

The ST(R)E(A)M Methodology in Kindergarten: A Teaching Proposal for Exploratory and Discovery Learning

Abstract: This paper attempts to present a proposal to teach the natural concepts of hydrodynamics under the ST(R)E(A)M approach. This is a comprehensive teaching proposal for pre-school teachers, with the possibility of implementation in each class, which helps the teacher to enrich his teaching with activities from science, technology, reading and writing, engineering and mathematics, promoting active participation, critical thinking, collaboration, creativity and developing skills necessary for tomorrow's citizens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…3) which is an attractive programmable floor robot for young children that is an easy way of introducing programming into the classroom and, its flexible nature also means that it can be used with children up to 8 years old and can help develop other areas of the curriculum in addition to ICT. Beebot is programmed with on-board buttons and can be programmed to move precisely in space by moving forward, backward, turning left and right while its simple and child-friendly layout makes it a perfect starting point for teaching control, direction (orientation) and programming language to young children (Foti, 2018, 2020, Foti, Rellia, 2020. Many schools have found that the Bee-Bot can help children develop computational thinking skills and/or reinforce concepts that other resources or methods do not use.…”
Section: Robots and Learning Environmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…3) which is an attractive programmable floor robot for young children that is an easy way of introducing programming into the classroom and, its flexible nature also means that it can be used with children up to 8 years old and can help develop other areas of the curriculum in addition to ICT. Beebot is programmed with on-board buttons and can be programmed to move precisely in space by moving forward, backward, turning left and right while its simple and child-friendly layout makes it a perfect starting point for teaching control, direction (orientation) and programming language to young children (Foti, 2018, 2020, Foti, Rellia, 2020. Many schools have found that the Bee-Bot can help children develop computational thinking skills and/or reinforce concepts that other resources or methods do not use.…”
Section: Robots and Learning Environmentsmentioning
confidence: 99%
“…Thereafter, the use of Technology (Technology) that can help facilitating human activities by modifying certain aspects of the natural world for daily needs, the use of Engineering (Engineering) as a process of designing, creating, and redesigning innovative products or processes, and Mathematics (Mathematics) skills including computation and decision making for problem-solving (Reeve, 2013) are the initial four elements of this methodology, with Arts (Art) being added which is artistic creation/expression through the arts, including expression and creativity in design. By the term Art, we do not only refer to the fine arts but also to culture, history, and the humanities in general (Foti, Rellia, 2020).…”
Section: Stem/steam/stream and Pedagogical Approachesmentioning
confidence: 99%
“…The goal of discovery learning is to motivate students to use the information and knowledge they have to resolve problems, and this can be done under a variety of different conditions. The basics principles of discovery learning according to Bruner (1961) in (Foti, 2021), As mentioned above, it is for students to interact with the environment, through the exploration and manipulation of materials, interactive discussions, and the conduct of experiments, as well as feel satisfied that they managed to resolve problems on their own.…”
Section: Introductionmentioning
confidence: 99%